Analysis of the capital structure across United States, Tokyo and Singapore. - Koh, Ting Wei. (2008)
The analysis in this research is based on data for five historical years from 1999 to 2003. The financial data for the companies listed on the New York Stock Exchange, Tokyo Stock Exchange and the Singapore Exchange were collected from an online database, Thomson Bankers’ Analytics. The objective is to compare the effects of independent variables on the dependent variable, leverage across the three exchanges.